Association between visual impairment and cognitive disorders in low-and-middle income countries: a systematic review. (3rd October 2021) - Gbessemehlan, Antoine; Guerchet, Maëlenn; Helmer, Catherine; Delcourt, Cecile; Houinato, Dismand; Preux, Pierre-Marie
Abstract: Objectives: Visual impairment and cognitive disorders are common among older people in Low-and Middle-Income Countries (LMIC). Several recent studies performed in High-Income Countries suggested that visual impairment is associated with cognitive disorders. However, no synthesis of current knowledge exists for LMIC. Methods: We have conducted an extensive literature search combining six databases and two grey literature databases. We searched for studies assessing the link between visual and cognitive impairments carried out in LMIC. The systematic search was performed up to 14th February 2019. Results: Overall, eight studies were included in this review. Among them, five studies were performed in Asia and seven studies had a cross-sectional design. Mean age of the participants varied from 64.2 to 76.2 years. Participants were most often females. Only three studies were specifically focused on the association between visual impairment and cognitive disorders. Out of the eight studies included, four reported a significant association; two showed a possible association and two did not retrieve any statistically significant effect. Heterogeneity in assessments of visual and cognitive impairments was high. Conclusion: In LMIC, very few studies explored the association between visual and cognitive impairments among older people. The current review seems to suggest that visual impairment is associated with cognitive disorders in LMIC. However, further studies are required to improve the knowledge on this relationship. Improving vision, in particular through optical correction and cataract surgery, could potentially be easy pathways to reduce cognitive disorders incidence and to improve quality of life of people affected by this disorder.